Выражение (3n/n-4-6n/n^2-8n+16): n-6/16-n^2+24n/n-4 !

ruslan2003185 ruslan2003185    1   04.10.2019 12:10    23

Ответы
xoxlogun1 xoxlogun1  27.08.2020 12:45

(3n/(n-4)-6n/(n^2-8n+16)):(n-6)/(16-n^2)+24n/(n-4)=(3n/(n-4)-6n/(n-4)(n-4))*(4-n)(4+n)/(n-6)+24n/(n-4)=(3n(n-4)-6n)/(n-4)(n-4)*(4-n)(4+n)/(n-6)+24n/(n-4)=(3n²-18n)/(n-4)(n-4)*(4-n)(4+n)/(n-6)+24n/(n-4)=3n(n-6)/(n-4)(n-4)*(4-n)(4+n)/(n-6)+24n/(n-4)=3n(4+n)/(4-n)+24n/(n-4)=3n(4+n)-24n/(4-n)=(12n+3n²-24n)/(4-n)=(3n²-12n)/(4-n)=3n(n-4)/(4-n)=-3n

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра